2011
DOI: 10.1007/s12149-011-0508-9
|View full text |Cite
|
Sign up to set email alerts
|

18F-fluoromisonidazole positron emission tomography before treatment is a predictor of radiotherapy outcome and survival prognosis in patients with head and neck squamous cell carcinoma

Abstract: Radiotherapy outcome and survival prognosis (radiotherapy or operation) in HNSCC may be predicted by carrying out [(18)F]FMISO PET before treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(41 citation statements)
references
References 28 publications
2
39
0
Order By: Relevance
“…The majority of studies involved FMISO measurements in head-and-neck cancer patients (Rajendran et al 2006;Rischin et al 2006;Thorwarth et al 2006;Eschmann et al 2007;Dirix et al 2009;Lee et al 2009;Kikuchi et al 2011;Zips et al 2012). Two other studies in head and neck used either FETNIM (Lehtio et al 2004) or FAZA .…”
Section: Exogenous Markers Of Hypoxiamentioning
confidence: 99%
“…The majority of studies involved FMISO measurements in head-and-neck cancer patients (Rajendran et al 2006;Rischin et al 2006;Thorwarth et al 2006;Eschmann et al 2007;Dirix et al 2009;Lee et al 2009;Kikuchi et al 2011;Zips et al 2012). Two other studies in head and neck used either FETNIM (Lehtio et al 2004) or FAZA .…”
Section: Exogenous Markers Of Hypoxiamentioning
confidence: 99%
“…Especially repeated hypoxic scans, before and during treatment, could give valuable information about the efficacy of PI3-K/AKT inhibition. Clinical studies in head and neck cancer patients have already shown that FMISO-PET uptake before or during radiotherapy correlates with outcome [120,121].…”
Section: Early Response Assessmentmentioning
confidence: 99%
“…Koh et al [221] , Liu et al [222] , Yeh et al [223] , Rischin et al [224] , Bentzen et al [125] , Rajendran et al [225] , Gagel et al [126] , Rajendran et al [226] , Hicks et al [227] , Lawrentschuk et al [200] , Loi et al [228] , Thorwarth et al [229] , Rajendran et al [230] , Rischin et al [231] , Thorwarth et al [232] , Zimny et al [124] , Eschmann et al [233] , Gagel et al [202] , Thorwarth et al [234] , Thorwarth et al [235] , Lee et al [236] , Lin et al [237] , Nehmeh et al [238] , Roels et al [239] , Dirix et al [240] , Lee et al [241] , Mortensen et al [127] , Wang et al [56] , Abolmaali et al [242] , Bowen et al [138] , Eary et al [243] , Kikuchi et al [244] , Hugonnet et al [131] , Yamane et al [245] , Mammar et al [246] , Zips et al [247] , Cheng et al [217] , Henriques de Figueiredo et al [248] , Okamoto et al [249] , Sato et al [218] , Segard et al [250] , Tachibana et al [251] , Norikane et al [219] [ Dubois et al …”
Section: F]fmisomentioning
confidence: 99%